In Defense of the Substance-Procedure Dichotomy - Jennifer S. Hendricks (Washington University Law Review, 2011)
John Hart famously observed, "We were all brought up on sophisticated talk about the fluidity of the line between substance and procedure,” but for most of Erie’s history, the Supreme Court has answered the question “Does this state law govern in federal court?” with a “yes” or a “no.” Beginning, however, with Gasperini v. Center for Humanities, and continuing with Semtek v. Lockheed Martin and the dissenting opinion in Shady Grove v. Allstate, a shifting coalition of justices has pursued a third path. Instead of declaring state law applicable or inapplicable, they have claimed for themselves the prerogative to fashion law that purportedly accommodates the interests of both sovereigns. With the cover of an intellectual critique of the substance–procedure dichotomy, the Court has thus embarked on a new phase of Erie doctrine, a phase that replaces “yes” or “no” with “Let’s see what we can work out.” This Article adds a new level of critique to the chorus of criticism that has already been directed at these opinions. It argues that the new enterprise and its blurring of the substance–procedure dichotomy are based on a misguided aspiration to accommodate state substantive policies at the expense of federal procedure. Descriptively, in order to have a dichotomy, it is necessary to have two poles. This Article therefore demonstrates that the distinction between substance and procedure is appropriately represented by a single-dimensional spectrum. Part of what the Court has done wrong is to ignore this linear relationship by insisting, for example, in Semtekthat res judicata is “too substantive” to be addressed in the Federal Rules yet procedural enough to be governed by federal common law under the Rules of Decision Act. In addition, given the linearity of substance and procedure, one could imagine the distinction either as a dichotomy of black and white, with every legal rule falling into one category or the other, or as a spectrum of gray, with many or even most legal rules falling in the mushy middle. Descriptively, of course, the latter view is more accurate. This Article argues, however, that the Court should nevertheless classify each legal rule as black or white, rather than try to accommodate both its procedural and its substantive aspects. This Article offers two reasons for preferring the black–white approach. First, the governing statutes contemplate a dichotomy between substance and procedure, and the Court is not authorized to use the ambiguity in that distinction to replace the statutory scheme with its own discretionary treatment of state law. Second, returning to the black–white approach would promote democratic transparency in the states. Specifically, in addition to traditional Erie concerns about judicial lawmaking, Congress has set a policy of establishing a uniform body of transsubstantive procedural law. State legislators know this, and there is nothing wrong with federal courts expecting them to act accordingly. If they, as Representative Dingell famously offered, prefer to manipulate procedure in order to undermine the substantive rights they purport to have created, the threat of fixed procedures in diversity could and should restrain them. Too often, the Supreme Court treats legislative enactments as fixed, so that the game begins when the litigants start their forum shopping. The game begins earlier, in the legislature, and the nascent effort to accommodate state law through Erie doctrine creates the wrong incentives for that game.
Keywords: Erie Railroad v. Tompkins 304 U.S. 64 (1938); Gasperini v. Center for Humanities 518 U.S. 415 (1996); Semtek International; Inc. v. Lockheed Martin Corp. 531 U.S. 497 (2001); Erie doctrine; Federalism; Preemption (Legislative power); Federal Rules of Civil Procedure; Rules Enabling Act of 1934; United States